Intrapersonal conflicts as the basis for the professional development of university students (by the example of a non-state university) - Sagitova Victoria Ravilꞌevna (Política e Gestão Educacional, 2021)
The purpose of writing this work is to cross-light the issue of predetermining the professional development of students, their self-determination by intrapersonal conflicts and crises. The paper presents a theoretical justification for intrapersonal conflicts through underlying contradictions. A conflict is presented as a dual phenomenon in the writings of the sociological school of conflictology. The contradictions and conditions that give rise to intrapersonal conflict in the process of professional self-determination are described. The paper presents the results of an empirical study conducted at a private university in the city of Kazan. Its results made it possible to confirm the key point that intrapersonal conflicts not only accompany professional self-determination and the formation of students, but also lead to the harmonization of the students’ personalities as professionals and allow them to realize the importance and necessity of training.